2018
DOI: 10.1051/0004-6361/201730995
|View full text |Cite
|
Sign up to set email alerts
|

Open clusters

Abstract: Context. Stellar physical properties of star clusters are poorly known and the cluster parameters are often quite uncertain. Aims. Our goals are to perform a spectrophotometric study of the B star population in open clusters to derive accurate stellar parameters, search for the presence of circumstellar envelopes and discuss the characteristics of these stars. Methods. The BCD spectrophotometric system is a powerful method to obtain stellar fundamental parameters from direct measurements of the Balmer disconti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 92 publications
1
45
0
1
Order By: Relevance
“…Our work suggests that some Be stars can be produced as a result of core contraction and surface rotational acceleration due to efficient AM transport. This single star scenario, proposed by Maeder & Meynet (2001), also explains the higher abundance of Be stars in slightly aged populations (older than 10 Myr) and stars near the TAMS (Keller, Bessell & Da Costa 2000;Aidelman et al 2018), because more envelope spin-up occurs as stars age and evolve toward the TAMS. Additionally, the larger abundance of Be stars in low-metallicity environments (Peters et al 2019 and references therein) is naturally explained by the smaller mass/AM loss through winds (rather than having to appeal to larger rotation rates at birth), allowing more stars to reach their breakup rotation rate.…”
Section: The Be Star Phenomenonmentioning
confidence: 83%
“…Our work suggests that some Be stars can be produced as a result of core contraction and surface rotational acceleration due to efficient AM transport. This single star scenario, proposed by Maeder & Meynet (2001), also explains the higher abundance of Be stars in slightly aged populations (older than 10 Myr) and stars near the TAMS (Keller, Bessell & Da Costa 2000;Aidelman et al 2018), because more envelope spin-up occurs as stars age and evolve toward the TAMS. Additionally, the larger abundance of Be stars in low-metallicity environments (Peters et al 2019 and references therein) is naturally explained by the smaller mass/AM loss through winds (rather than having to appeal to larger rotation rates at birth), allowing more stars to reach their breakup rotation rate.…”
Section: The Be Star Phenomenonmentioning
confidence: 83%
“…The rapid rotation that characterizes Bn stars, the occasional appearance of some emission in the Balmer lines (at least in Hα), and the presence of signatures for some sBD are motivate us to think that Bn and Be probably belong to the same class of objects. Some attempts to show a possible correlation between fastrotating late B-type stars and Be stars based on the presence of a sBD were discussed by Aidelman et al (2018) in open clusters.…”
Section: Bn Starsmentioning
confidence: 99%
“…Contrarily, in the diagrams where the parameters were corrected for rotational effects, we see that Bn stars can have age ratios 0.2 (t/t MS ) Bn 0.8 if M/M 4, whereas they have 0.0 (t/t MS ) Bn 0.2 for masses M/M 5. According to Aidelman et al (2018), the Be phenomenon is observed along the whole MS, and appears on average at an earlier age in massive stars than in the less massive stars. Thus, the possibility that the most massive Bn stars display the Be phenomenon at any time should not be excluded.…”
Section: Distribution Of Stellar Ages In Our Samplementioning
confidence: 99%
“…There is only one study based on CCD photometry with UBVRI data performed by Sagar & Cannon (1997). We refer the reader to the very recent study of Aidelman et al (2018) for a complete compilation of the parameters of the cluster determined by different authors, using different data and techniques.…”
Section: Ngc 6087mentioning
confidence: 99%